Constructing Character: The Implementation of Constructivist Learning in Islamic Moral Education - Afida Fitrotul Mu'afah; Moh. Irmawan Jauhari; Ahmad Khoirul Mustamir; Fadhil Akbar; Aji Wahyudin (Al-Qalam Institue, 2026)
This study aimed to examine how constructivist learning was planned, implemented, and evaluated in Akidah Akhlak instruction and how it contributed to students’ character formation. Moral education remains dominated by memorization, creating a gap between religious knowledge and conduct. Constructivist pedagogy offers contextual, dialogic, and reflective learning for developing moral reasoning and value internalization. A qualitative single-case study was conducted at Madrasah in east Java. Data were collected through nonparticipant observations, semi-structured interviews, and document analysis, then analyzed using condensation, display, and verification. Findings showed that moral dilemmas activated prior knowledge and increased participation. Collaborative discussion enabled students to compare perspectives and justify moral choices. Teacher scaffolding deepened reasoning, although direct explanation occasionally reappeared. Reflection connected classroom concepts with personal commitments, but its depth varied. Institutional policies and learning documents supported value-oriented instruction. However, uneven planning, broad assessment indicators, limited professional development, and partial coordination constrained consistency. Theoretically, the study advances an integrated model linking experience, dialogue, scaffolding, reflection, and institutional support. Practically, it highlights the need for structured facilitation, authentic assessment, and cross-context reinforcement to sustain character development.